2005
DOI: 10.1097/00128360-200504000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection and p16INK4a Protein Expression in Vulvar Intraepithelial Neoplasia and Invasive Squamous Cell Carcinoma

Abstract: Upregulation of INK4a gene occurs in vulvar carcinogenesis. p16(INK4a) is not a sensitive marker for differentiation of benign vulvar squamous epithelium from condyloma acuminatum or VIN 1 lesions because most VIN 1 lesions are p16(INK4a) negative. Expression of p16(INK4a) may aid in the diagnosis of HPV-related lesions and as such may be of value as a surrogate marker in the diagnosis of vulvar premalignant and malignant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 17 publications
2
21
1
1
Order By: Relevance
“…Thin-section microtome sections were prepared from biopsy tissue and sections adjacent to those used for histologic diagnosis were tested for HPV DNA to ensure genotyping was done on abnormal tissue. VIN lesions were obtained from women in developed and developing countries, whereas most other studies to date have examined the distribution of HPV types in VIN lesions from a single region or medical institution (4)(5)(6)(26)(27)(28)(29)(30).…”
Section: Cancer Epidemiol Biomarkers Prev 2009;18(6) June 2009mentioning
confidence: 99%
“…Thin-section microtome sections were prepared from biopsy tissue and sections adjacent to those used for histologic diagnosis were tested for HPV DNA to ensure genotyping was done on abnormal tissue. VIN lesions were obtained from women in developed and developing countries, whereas most other studies to date have examined the distribution of HPV types in VIN lesions from a single region or medical institution (4)(5)(6)(26)(27)(28)(29)(30).…”
Section: Cancer Epidemiol Biomarkers Prev 2009;18(6) June 2009mentioning
confidence: 99%
“…INK4a has been described in VIN [21][22][23] and is thought to arise from interaction of the viral protein E7 with Rb, thus inhibiting Rb function, which results in upregulation of p16 INK4a . Although p16 upregulation is a very sensitive marker for VIN, it does not result in downregulation of the cell cycle because downregulation of its downstream effectors cyclinD1 and cyclinD2 is successfully neutralized by upregulation of cyclinE1, cyclinE2, cyclinA2, cyclinB1 and cyclinB2.…”
Section: Ink4amentioning
confidence: 99%
“…Multiple authors have suggested that vulvar cancer comprises two separate diseases, the first type occurring with high prevalence among young women and developing from vulvar intraepithelial neoplasia caused by HPV, and a second type afflicting older women and developing from non-neoplastic epithelial disorders such as lichen sclerosus or chronic inflammation. [2][3][4]12,13,15,18,24,25 However, these studies of HPV prevalence in invasive squamous vulvar carcinoma also utilized different methods of detection, including in-situ, [13][14][15][16][17][18] dot blot, 20,21 and Southern blot 20 hybridization, immunohistochemistry, 15 and PCR-based assays, 2,7,12,18,19,[22][23][24][26][27][28][29][30][31][33][34][35][36] each with different analytic sensitivities. Moreover, the particular HPV genotype(s) targeted in previous work is inconsistent between studies; many early reports documented only HPV16, 18, 33, and/or 6/11, 18,20,21,26,[28][29]…”
mentioning
confidence: 99%
“…12,22 Also, some studies tested only a few cases of invasive squamous vulvar carcinoma, which limits the predictive value of the resulting data. 14,17,21,23 Despite these shortcomings, this body of work indicates that HPV16 is the most common genotype present in invasive squamous vulvar carcinoma. 2,7,[16][17][18][19]22,24,[26][27][28][29][30][31] The prevalence of other high-and low-risk HPV types in invasive squamous vulvar carcinoma, however, remains less certain.…”
mentioning
confidence: 99%
See 1 more Smart Citation